Features of the leading system of wheat seedlings under stress of the oil - Писаренко, П. В.; Колєснікова, Л. А. (Scientific Progress & Innovations, 2012)
Defined morphological manifestations of toxic and inhibitory properties of the components of crude oil leaf blade cross-section (hereinafter – LP) wheat seedlings The dynamics of formation of the conduction system LP fourth leaf model of agricultural test culture in the early stages of ontogeny in the presence of stressors. Established that soil contamination crude oil at a dose of 5 ml/kg observed stimulation of the elements of mechanical tissue LP, which is manifested in the growth of their size and quantity. Moderate pollution (10–20 ml/kg) causes an asymmetry – tropism placement SVP is relatively large central SVP, reduce the size of big farm support while increasing that of the average SVP, accumulation of elements of mechanical tissue. Increasing doses of oil pollution to 50 ml/kg significantly affect the development of leading LP and leads to the appearance of emptiness and phloem elements xylem medium and large SVP fine masses, which probably formed products of dissimilation, degradation and catabolism.